Selective Screening for Metabolic Disorders in the Slovenian Pediatric Population - Lampret, Barbka Repič (J Med Biochem, 2015)
BACKGROUND: Inborn errors of metabolism (IEM) are disorders with a block in the metabolic pathway caused by a genetic defect of a specific enzyme. Although each of these diseases is quite rare, as a group they account for a significant proportion of newborn and childhood morbidity and mortality. Early diagnosis is important to prevent complications or even death of the child. Selective screening is an important diagnostic tool for the diagnosis of IEM. METHODS: In Slovenia, symptomatic patients with suspected IEM are referred to the University Children’s Hospital Ljubljana. Techniques used for selective screening are gas chromatography-mass spectrometry, ion exchange chromatography-post-column derivatization, liquid chromatography-tandem mass spectrometry and isoelectric focusing. Fluorimetric method is used for enzyme activity measurement. RESULTS: There are 168 patients with amino and organic acidemias, 5 patients with disorders in fatty acids metabolism, 1 patient with a congenital disorder of glycosylation, 42 patients with Fabry disease (of which 37 are adult) and 20 patients with Gaucher disease (of which 18 are adult) in the Slovenian Register for Rare Diseases. CONCLUSIONS: In Slovenia, management of patients with IEM is centralized at the University Children’s Hospital, with the exception of adult patients with Fabry and Gaucher disease. The team work is well organized with close cooperation between the laboratory and pediatricians specialized in metabolic disorders. According to the known frequencies of IEM from the literature, we would expect more positive results than obtained. To evaluate these results, we are planning to perform a pilot study on expanded newborn screening.